Explaining Recent Trends in US School Segregation - Caetano, Gregorio; Maheshri, Vikram (Journal of Labor Economics, 2023)
From 2002 to 2018, the fraction of minority-segregated public schools in the United States roughly doubled, but the fraction of White-segregated schools decreased at an even faster rate. Endogenous segregation fueled by parents choosing schools on the basis of their racial compositions can in principle dwarf all other determinants of segregation over time because of social multiplier effects. However, we find that demographic change from Hispanic immigration has been the biggest driver of these trends. These findings are particularly pronounced in urban areas, which experienced the largest changes in segregation and are where policy makers are most concerned about the pernicious effects of segregation.